(untitled) (Medical Forum Monthly, 2020)
Objective: Cadmium (Cd), a heavy metal has a potential to develop toxicity in various organs especially kidney and liver. Serious toxicity of cadmium became the centre of attention because of its association with neoplastic and non-neoplastic lesions in various organs and tissues. The objective of this study was to evaluate the detrimental effects of cadmium on kidney leading to increased urinary proteins and serum creatinine. Study Design: An experimental study on albino mice Place and Duration of Study: This study was conducted at the Department of Morbid Anatomy and Histopathology; University of Health Sciences, Lahore for 8 weeks in the year 2014. Materials and Methods: Albino mice (n=72) were randomly divided in groups as control group and 5 experimental groups A, B, C, D and E with 12 mice in each group. In this experiment, cadmium was used as anhudrous cadmium chloride (CdCl2) orally and intraperiotoneally on alternate days for 8 weeks in a dose of 5mg/kg body weight. Bovine serum albumin was also used once in group D to induce serum sickness leading to development of glomerular damage. Results: This experimental work revealed the biochemical alterations in kidney like proteinuria and serum creatinine because of cadmium. However, these biochemical changes were proportional to the dose and route of introduction of cadmium chloride. Conclusion: Cadmium is a toxic heavy metal that can lead to progressive renal failure. Cadmium toxicity leads to progressive damage to glomeruli. In this study biochemical changes were observed that were proportional to different doses of cadmium. As this chemical is a naturally occurring toxicant that exists everywhere in air, soils, foodstuff and water, hence to control the emission of this toxicant should be of high priority for better healthcare of community.